First sighting of the white-tailed eagle Haliaeetus albicilla (Linnaeus, 1758) for Makwanpur District, Nepal - Pradhan, Nikeet; Rokka, Prashant; Bajgain, Santosh; Pradhan, Aavas (Nepalese Journal of Zoology, 2022)
The white-tailed eagle Haliaeetus albicilla is a rare winter visitor to Nepal and it has been previously recorded from Chitwan, Kathmandu, Nawalparasi, Bardiya, Sunsari and Kaski districts of Nepal. Here, we present the first-ever record of the white-tailed eagle for the Makwanpur District of Nepal. During the bird survey by line transect method, we observed a single juvenile of the species soaring over the Manahari River on 29 January 2022. Loss of habitat, illegal fishing, human disturbance, extraction of boulders, gravel, sand and water pollution were the major threats to birds observed during the survey period. In order to overcome these threats, conservation awareness programs about the importance of birds, effective law enforcement, and regular monitoring should be carried out in the study area.